Pharmaceutical drugs and other substances with pharmacological activity in the environment: a threat to biodiversity? - Nunes, Bruno (Conservation Science, 2015)
Drugs of human origin are now dispersed in all ecosystems, and non-target exposed biota are likely to be impacted in the future by a large number of substances with unpredictable consequences. One of the potential effects of drugs (and other substances with pharmacological activity) is the exertion of selective pressure, favouring an artificial process of selection, in which sensitive organisms may be favoured. We bring to discussion the consequences expected from chronic environmental exposure of biota to two major classes of chemicals that are nowadays released thoroughly into the environment: stimulants and neuroendocrine drugs. Conservation Science Vol.2(1) 2014: 12-16